Environmentally friendly membrane based on chitosan, citric acid, and calcium for slow-release fertilizer - Taufik Abdillah Natsir; Alvina Mita Iknawati; Iqbal Dian Wanadri; Dwi Siswanta; Retno Ariadi Lusiana; Sari Edi Cahyaningrum (Heliyon)
In agriculture, fertilizers are important for plant growth. Among them, conventional fertilizers, particularly urea fertilizers, are popular owing to their low cost and high nitrogen content. However, their use often leads to uneven nitrogen absorption and environmental pollution. Slow-release fertilizers (SRFs), particularly those based on chitosan, offer a solution. This research aims to produce biodegradable chitosan/citric acid/calcium–urea (CS/St/Ca–urea) films to increase the absorption efficiency and use of artificial nitrogen fertilizers (especially urea). Herein, chitosan/citric acid/calcium (CS/St/Ca) films were synthesized and applied as SRFs. Chitosan was dissolved in 1 % acetic acid and added to citric acid at 55 °C for 24 h. Then, calcium oxide (CaO) and urea were added to the CS/St mixture and stirred until homogeneous. Subsequently, the membrane product was characterized by ATR–IR, SEM–EDX, and elemental analysis and its nitrogen solubility was determined using a UV–vis spectrophotometer. The physical properties of the CS/St/Ca were investigated via swelling, hydrophobicity, and tensile strength tests. Results showed that a CS/St at weight ratio of 1:1 can increase the tensile strength by up to 13.6 %. The addition of a filler with a Ca additive, as well as the addition of CaO, can increase the mechanical strength of the membrane. The CS/St/Ca film membranes can function optimally as a urea SRF coating material with a release rate of 3.37–9.46 ppm day−1. The applied kinetic model follows the Higuchi kinetic model, with an R2 value of 0.9505.